Pattern of Adverse Drug Reactions — An Observational Study in A Tertiary Care Teaching Hospital (The Planet, 2024)
Introduction: ADR is defined as "A response to a drug which is noxious and unintended, and which occurs at doses normally used in man for the prophylaxis, diagnosis, or therapy of disease, or the modifications of physiological function". It is the undesirable effect of medicine that occurs beyond its known therapeutic effects. This study aimed to analyze the pattern of adverse drug reactions among the study respondents. Methods and materials: This observational study was conducted at the Department of Pharmacology, Dhaka Medical College, Bangladesh, from July 2019 to June 2020. A total of 600 patients were selected by purposive sampling technique as per inclusion and exclusion criteria. Collected data were analyzed using descriptive statistics. Analysis of data was carried out by using a statistical package for social science (SPSS) 22.0 for Windows. Result: Out of 600 patients, adverse drug reaction was detected in 16 (2.70%) patients. Among the three departments, the highest number of patients with ADR was detected in the pediatrics department (56.3%). Steven Johnson syndrome was the most common ADR (4, 25.0%), followed by each drug-induced rash and hypersensitivity (3, 18.8%). 4 (25.0%) were mild in severity, 9 (56.3%) were moderate and 3 (18.7%) were severe, and the predominant body system affected by ADRs was dermatology (8, 50%). Positive de-challenge was observed in 14 (87.5%) cases with ADR and positive re-challenge was observed in 2 (12.5%) cases. Moreover, 62.5% of ADRs were developed by oral route. Conclusion: The most frequently experienced ADR is Steven Johnson's Syndrome, which predominantly occurs through the oral route. The prominent department is the pediatric department, and a majority of the cases are moderate in severity. Moreover, dermatology is the most commonly affected body system. This study also states that a vast number of ADR cases recover after withdrawing the offending drug.
Keywords: Adverse drug reaction; Steven Johnsons Syndrome; Dermatology; Toxic epidermal necrolysis